Exploring Informal Social Institutions Supporting Informal Skills Learning - Baral, Durga Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This study examines the role of informal social institutions in facilitating informal skills learning within the informal work settings of Nepal, an area that remains underexplored in the current literature. Drawing on the theoretical frameworks of Coleman’s (1988) social capital and Lave and Wenger’s (1991) situated learning, the research highlights how family and senior artisans as gurus, workplace dynamics, social networks, and cultural practices significantly influence the learning pathways and employment outcomes of informal learners, who are predominantly from vulnerable groups and typically exit formal education early. Using in-depth conversational interviews (Kurakani) and work observations with 14 research participants, the study focuses on four key sectors—pottery, metalcrafts, fast food, and two-wheeler mechanics. It illuminates the crucial yet often less visible support these institutions provide. In these settings, culture functions as a holistic system, where shared values, beliefs, and traditions (including religious norms) shape not only the skills that are transmitted but also the methods and meanings of learning itself. The findings advocate for policies that acknowledge and integrate the dynamics of informal social institutions to enhance the effectiveness of Technical and Vocational Education and Training (TVET) programs in developing contexts like Nepal. The insights derived not only contribute to academic discourse but also offer practical implications for policymakers and educators aiming to optimize TVET strategies to better serve marginalized populations.